The Prevalence of Metabolic Syndrome in Iran: A Systematic Review and Meta-analysis - Saeideh MAZLOOMZADEH; Zahra RASHIDI KHAZAGHI; Nouraddin MOUSAVINASAB (Tehran University of Medical Sciences, 2018)
Background: Metabolic syndrome (MS)is a collection of metabolic disorders which leads to early cardiovascular disease and diabetes type II. Regarding the wide range of its prevalence in Iran, this systematic review and meta-analysis determined the overall prevalence of the metabolic syndrome in Iran. Methods: In this systematic review and meta-analysis, the Medline, ISI, IranMedex, and SID were searched using "metabolic syndrome", "syndrome X", "prevalence", and "Iran" keywords from 2002 to 2012. A total of 223 articles were found in which 14 studies were considered for meta-analysis. Data were analyzed using fixed and random model and meta-regression in STATA. Results: The prevalence of MS for those who were 20 yr and older was 23. 8% (95%CI: 18. 99-28. 67) and in under 20 was 10. 98% (95%CI: 7. 75-14. 2). Metabolic syndrome was more frequent in women (25. 5%) than in men (17. 16%) and was increased with increasing age. The most frequent component of metabolic syndrome was low HDL cholesterol (59. 7%) followed by hypertriglyceridemia (39. 5%). Conclusion: Regarding a high prevalence of metabolic syndrome and some of its components such as low HDL and high triglyceride in our country, implementation of programs for metabolic syndrome prevention is necessary.